Paciente de sexo femenino de 2 años de edad, con desnutrición proteico calórica y anemia. - Tomala Olaya, Sandy Izamar (2021)
This case presents a female patient of 2 years 8 months of age with a diagnosis of protein-calorie malnutrition and anemia, in the clinical case a comprehensive nutritional assessment is carried out, in order to obtain the diagnosis in which the patient is and from this way to adapt a nutritional treatment. The objective is to improve the nutritional status in patients with protein-calorie malnutrition and anemia to avoid future risks. Protein-calorie malnutrition is caused by low consumption of foods lacking in protein and calories for a long time. Among the possible causes of malnutrition it can be difficult access to food, disorders or drugs that interfere with the consumption, processing (metabolism) or absorption of nutrients. In children, nutritional marasmus or protein-calorie malnutrition is more frequent. In the nutritional assessment that was carried out, it was found in the anthropometric, chronic malnutrition, in the biochemical values the patient presents anemia, in the clinical aspect she has paleness, recessed skin, and abdominal depletion, in the dietary aspect, low food consumption is observed, the mother does not provide adequate portions and frequency of meals.